Geohydrologic units of Ischia Island (Southern Tyrrhenian Sea, Italy) - Silvia Fabbrocino; Eliana Bellucci Sessa; Sandro de Vita; Rosario Avino; Antonio Carandente; Enrica Marotta; Fabio Todisco; Mauro Antonio Di Vito (Journal of Maps)
The first hydrogeological mapping of Ischia Island at the 1:10,000 scale is presented and discussed. The ‘Map of the geohydrologic units of Ischia Island’ and the accompanying hydrostratigraphic sequence at a basin scale are based on the most recent geological maps and data from the CAR.G Project, and on new volcanological and hydrogeological surveys and studies. Data sources include the database stored by the INGV, Sezione di Napoli, Osservatorio Vesuviano and field investigations, including a survey of the springs and thermo-mineral springs which has been neglected up to now. In total 130 volcanostratigraphic units and 18 geohydrologic units were recognized; the distribution of fumaroles sites was enhanced, and 60 springs/thermal springs were identified/rediscovered. The proposed hydrogeological map provides an overview of the volcano-tectonic evolution of Ischia Island and upgrades the hydrogeological model, becoming a catalyst for the effort to acquire better data and to manage natural both resources and risks.